Analisis Kemampuan Penalaran Matematis Siswa SMP Kelas VIl dalam Menyelesaikan Soal Cerita Ditinjau dari Persepsi Siswa - Lily Rahmawati; Yesi Franita; Megita Dwi Pamungkas (Universitas Pekalongan, 2023)
The purpose of this study was to analyze the mathematical reasoning ability of seventh grade junior high school students in solving story problems in terms of student perceptions. This research used qualitative method with descriptive approach. The subjects in this study were 31 students of class VII A SMP N 5 Magelang with the selection of subjects using purposive sampling technique. The instruments used were observation sheets, which were used to observe the mathematics learning process, questionnaires of students' perceptions of mathematics, mathematical reasoning ability tests, interview guidelines, and documentation. The stages of data analysis in this study include data collection, data reduction and data presentation. Meanwhile, to check the credibility of data using triangulation techniques. The data generated in this study are data on the results of students' perceptions of mathematics, data on the results of mathematical reasoning ability tests on whole numbers and fractions, and interview transcripts with research subjects. The results of this study show that students with very positive perceptions with high reasoning ability and students with positive perceptions with high reasoning ability are able to explain orally all indicators of mathematical reasoning but are unable to explain in writing the indicators of determining strategies